Redescription of the rare shrimp Heterocarpus nesisi (Burukovsky, 1986 (Crustacea: Caridea: Pandalidae) rediscovered off western Mexico, with the proposal of a new genus - Hendrickx, M.e. (Zootaxa, 2019)
A rare species of pandalid shrimp, Heterocarpus nesisi Burukovsky, 1986, is rediscovered in deep water off western Mexico. Previous to this capture, this species was known only from the holotype, a mature male captured at 800 m depth, originally described in the genus Heterocarpus and later transferred to Plesionika. A second, unconfirmed record, was provided in 1989: a female captured at 898 m near the southern tip of the Baja California Peninsula. Heterocarpus nesisi is redescribed and appendages are illustrated. The general morphology of this species makes it difficult to fit within Heterocarpus or Plesionika, and a new genus, Heteronika gen. nov., is proposed to accommodate it. Heteronika nesisi is associated with the lower boundary of the Oxygen Minimum Zone occurring off western Baja California.